Resilience and Stress Management as Determinants of MSME Managers’ Adaptive Behavior in the Era of Digital Transformation - Heldy Vanni Alam; Rezkiawan Tantawi; Amelia Kaluku; Dwi Aminarti Maele (Jambura Science of Management, 2026)
Purpose: The research examines the urgency of digital transformation, which is rapidly affecting the Micro, Small, and Medium Enterprises (MSMEs) sector. As the backbone of the local economy in Gorontalo Province, MSMEs face significant challenges in adapting to technological, market, and regulatory changes. Psychological factors such as resilience and stress management are presumed to play a crucial role in shaping the adaptive behavior of MSME managers in responding to these changes. The purpose of this study is to analyze the influence of these two psychological variables on the adaptive behavior of MSME managers and to identify the factors that most significantly contribute to their readiness to face digital transformation.Design/Methodology/Approach: The research employed a quantitative approach using multiple regression analysis on survey data from 150–200 MSME actors. The findings reveal that personal strength, social support, coping strategies, and optimism significantly influence adaptive behavior. In contrast, factors such as emotional regulation, impulse control, stress awareness, and negotiation ability do not show a meaningful effect.Findings: The resulting model explains 67.3% of the variance in change behavior, with personal strength emerging as the most dominant predictor. These findings indicate that readiness for change is more strongly determined by practical and psychological reinforcement factors rather than reflective ones. Therefore, interventions aimed at strengthening MSMEs should focus on enhancing personal resilience, developing coping strategies, optimizing social support, and fostering an optimistic outlook.